"Invisibility is not a natural state for anyone": (Re)constructing narratives of Japanese American incarceration in elementary classrooms. Issue 4 (7th August 2020) - Rodríguez, Noreen Naseem
Abstract: Difficult histories that may contradict national values are rarely taught in elementary schools. This comparative study of two elementary educators examines their pedagogical approaches to the teaching of Japanese American incarceration as difficult history. Framed by Asian American critical race theory, the teachers' practices revealed challenges in teaching Japanese American incarceration as an example of a difficult history. The author interrogates the role of counternarratives and empathy in teaching difficult histories, particularly with young children, and offers suggestions for pedagogies of discomfort that reveal difficult histories while fostering critical hope.